Bag Charm dari Kawat Bulu - Muhammad Yasin; Riski Himawan; Melinda Wirastiti; Verinda Yelanita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Bag charm is a fashion accessory that is on the rise because of its ability to beautify the appearance of the bag and provide a unique personal touch. In recent years, these accessories have become a significant trend in the fashion world, especially thanks to the influence of social media such as TikTok and Instagram. One of the interesting innovations of bag charm is the use of bristle wire (pipe cleaner) as the main material, which allows the creation of various interesting shapes such as flowers, animals, and funny characters. The business proposal